Unicystic ameloblastoma: a late recurrence with pseudo-glandular features. A case report. - Khoo, S.P.; High, A.S.; Awang, M.N. (1995)
A case of unicystic ameloblastoma which recurred after 15 years showing unusual histological features is reported. The prominent pseudo-glandular features present are described. This case highlights the importance of extensive histological examination for more characteristic features of ameloblastoma to reach a correct diagnosis.